A micromechanics-based model for deformation-induced damage and failure in elastomeric media. (May 2021) - Guo, Qiang; Zaïri, Fahmi
Abstract: In order to predict damage and failure in elastomeric media, a new physically-based model based upon a multiscale approach is proposed. The behavior of polymer chains is described by means of statistic mechanics, in which the stretchability and detachability of the internal bonds are introduced to account for the enthalpy contribution to chain elasticity and the time-dependent stochastic process of chain scission, respectively. The complex but inevitable coupling effect between the chain conformation change and the bond length change is addressed in a rigorous approach, and the bond rupture is treated as an energy activation process that is related to the thermal oscillation and stimulated by the chain stretch. The micro-macro transition is realized with a non-affine microsphere-based strategy where the length variability of polymer chains is considered statistically, as well as its evolution with the loading histories. The model is firstly used to discuss some history-dependent features (Mullins effect and monotonic biaxial failure) of rubbers in relation to damage accumulation due to progressive chain scission events. The efficiency of the model is then critically discussed by comparisons with a few illustrative experiments of different rubbery media under high thermal environmental and thermal aging effects. To illustrate further the predictive capability of the model, the failure of rubbers is finally treated under a wide range of biaxial loading conditions. Highlights: We propose a micromechanics-based model for deformation-induced damage and failure of rubbers. We introduce the stretchable and detachable bonds to capture the behavior of polymer chains. We perform simulations to reproduce Mullins effect and monotonic biaxial failure. We account for the high thermal environmental and thermal aging effects on damage and failure.